Progestin-Based Protocol for Synchronization of Follicular Wave Emergence in Buffaloes During Summer and Winter - Gimenes, Lindsay Unno [UNESP]; Tonizza de Carvalho, Nelcio Antonio; Soares, Julia Gleyci; Chiaratti, Marcos Roberto; Macabelli, Carolina Habermann; Ferraz, Marcio Leao; Souza, Diego Cavalcante de; Ayres, Henderson; Baruselli, Pietro Sampaio (Int Buffalo Information Ctr, 2013)
The aim of the present study was to evaluate the effects of type of norgestomet auricular implant (new - N or previously used during 5 days - U), season of the year (summer - S and winter - W), and parity (12 heifers - H and 23 cows - C) on synchronization of follicular wave emergence in buffaloes. For this purpose, 35 buffaloes were examined daily by ultrasonography until follicular wave emergence was detected. Data were analysed by ANOVA, using PROC GLIMMIX. No interactions were observed in none variables. Time of follicular wave emergence and number of follicles at emergence were not affected by type of implant or season of the year. Parity also did not influence the number of follicles at emergence. However, follicular wave emergence occurred later in heifers than in cows. In conclusion, the previous use of a norgestomet auricular implant independent of the season of the year does not affect the time or the number of follicles at follicular wave emergence in buffaloes. Nevertheless, although heifers and cows had a similar number of follicles at emergence, the time of follicular wave emergence occurs earlier in cows than in heifers.
Keywords: auricular implant; Buffalo; follicular wave; progestin; synchronization